Antenas multibandas utilizando a geometria fractal do tri?ngulo de Sierpinski - Matos, Rodrigo de Oliveira (2012)
In this dissertation will be presented two configurations for antennas using a Sierpinski fractal geometry for multiband operation. The adopted geometry, with the successive generation of the triangles with predefined angle, it has a logarithmic spacing between the operation frequencies. These projects were built with a fiber glass substrate FR4 and provide acceptable performance in terms of return loss at different frequency bands. It is presented simulations and measurements of the fabricated prototypes. Moreover, it is shown the antenna parameters like bandwidth, directivity, gain, radiation efficiency and radiation pattern.